Removal of Foley Catheters in Live Donor Kidney Transplant Recipients on Postoperative Day 1 Does Not Increase the Incidence of Urine Leaks - Siskind, Eric; Sameyah, Emil; Goncharuk, Edwin; Olsen, Elizabeth M.; Feldman, Joshua; Giovinazzo, Katie; Blum, Mark; Tyrell, Richard; Evans, Cory; Kuncewitch, Michael; Alexander, Mohini; Israel, Ezra; Bhaskaran, Madhu; Calderon, Kellie; Jhaveri, Kenar D.; Sachdeva, Mala; Bellucci, Alessandro; Mattana, Joseph; Fishbane, Steven; D'Agostino, Catherine; Coppa, Gene; Molmenti, Ernesto (International Journal of Angiology, 2013)
Catheterization of the urinary bladder during kidney transplantation is essential. The optimal time to remove the Foley catheter postoperatively is not universally defined. It is our practice to remove the Foley catheter on postoperative day 1 in live donor kidney transplant recipients who meet our standardized protocol criteria. We believe that early removal of Foley catheters increases patient comfort and mobility, decreases the risk of catheter associated urinary tract infections, and allows for decreased hospital length of stay. The hypothetical risk of early removal of Foley catheters would be the increased risk of urine leak. We reviewed 120 consecutive live donor kidney transplant recipients and found that there was not an increased incidence of urine leaks in patients whose Foley catheters were removed on postoperative day 1.
Keywords: Foley; urine leak; kidney transplantation; Doppler ultrasonography; outcomes